2016
DOI: 10.1016/j.visres.2016.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Crowding in the S-cone pathway

Abstract: The spatial extent of interference from nearby object or contours (the critical spacing of “crowding”) has been thoroughly characterized across the visual field, typically using high contrast achromatic stimuli. However, attempts to link this measure with known properties of physiological pathways have been inconclusive. The S-cone pathway, with its ease of psychophysical isolation and known anatomical characteristics, offers a unique tool to gain additional insights into crowding. In this study, we measured t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 69 publications
3
11
0
Order By: Relevance
“…Figure 6 extends this analysis more precisely into the fovea, plotting our own data (fitted with model #5) and those from several studies from Table 1 . The dotted line is based on foveal results from contrast thresholds of blurred stimuli, revealing a “size-limited” regime, which also matches results from non-strabismic amblyopia 26 , non-foveal AMD patients 55 and S-cone isolating stimuli 56 . For results on this line, critical spacing is proportional to stimulus size, such that critical spacing = 1.4 × size, a straight line parallel to the identity line on this log-log plot.…”
Section: Discussionsupporting
confidence: 64%
“…Figure 6 extends this analysis more precisely into the fovea, plotting our own data (fitted with model #5) and those from several studies from Table 1 . The dotted line is based on foveal results from contrast thresholds of blurred stimuli, revealing a “size-limited” regime, which also matches results from non-strabismic amblyopia 26 , non-foveal AMD patients 55 and S-cone isolating stimuli 56 . For results on this line, critical spacing is proportional to stimulus size, such that critical spacing = 1.4 × size, a straight line parallel to the identity line on this log-log plot.…”
Section: Discussionsupporting
confidence: 64%
“…In an attempt to reconcile the finding of Harrison and Bex (2014) with the other studies cited in Figure 8 , we identified several experimental parameters in their study that were different from the others cited in Figure 8 . First, although their target was also a single letter that could be presented in one of four orientations, unlike the other studies, their flankers were not the same as ( Chung & Mansfield, 2009 ; Coates et al., 2013 ; Coates & Chung, 2016 ; Kooi et al., 1994 ) or highly similar to ( Tripathy & Cavanagh, 2002 ; Tripathy et al., 2014 ) their target. Instead, they used a set of 17 letters presented in their upright positions as flankers.…”
Section: Effects Of Stimulus Parameters On Critical Spacingmentioning
confidence: 92%
“…The different symbols indicate eccentricity (circles: fovea, stars: 3 degrees, triangles: 5 degrees, squares: 10 degrees) for the contrast experiments ( Coates et al., 2013 ). The four S-cone points ( Coates and Chung, 2016 ) indicate results from 0, 3, 5, and 8 degrees eccentricity, respectively, from lowest to highest on the plot. The dotted and dashed lines show theoretical predictions from Song et al.…”
Section: Effects Of Stimulus Parameters On Critical Spacingmentioning
confidence: 99%
See 2 more Smart Citations